SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA BERPRESTASI PADA SMK RAKYAT PANCUR BATU DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Rieska Inryani Br Ginting; Zekson A Matondang (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2020)
The selection of high achieving students is a process that is very good for the school and thestudents themselves aiming for the continuity of education pursued. The selection of outstandingstudents takes place every year in the school of SMK Rakyat Pancur Batu Medan. In the process ofselecting scholarships achievers, the school provides the terms or criteria for prospectivescholarship recipients. The assessment team has come from the school, namely from each student'shomeroom teacher and administration to select the grades from the students. However, theassessment process of each student candidate is still done manually so far, so it requiresconsiderable time to process data. Based on this, a decision support system was used to carry outthe selection process for outstanding scholarship selection at SMK Rakyat Pancur Batu Medan.